A systematic review on heavy metals contamination in Bangladeshi vegetables and their associated health risks - Nowar, Abira; Islam, Md. Hafizul; Islam, Saiful; Jubayer, Ahmed; Nayan, Md. Moniruzzaman (Frontiers in Environmental Science, 2024)
This systematic review aimed to identify the heavy metal contents of Bangladeshi vegetables and evaluate the subsequent health hazards of these heavy metals. Relevant studies were obtained from systematic searches of electronic databases. Average (mean) concentrations of Arsenic (AS), Lead (Pb), Cadmium (Cd), Chromium (Cr), Manganese (Mn), Nickel (Ni), Zinc (Zn), and Copper (Cu) in the vegetables were calculated on a fresh-weight basis. The health hazards associated with these metals’ intake were assessed using estimated daily intake (EDI) and carcinogenic and noncarcinogenic risks were measured as the target cancer risk (TR), target hazard quotient (THQ), and hazard index (HI). The results showed that the mean concentration of As, Pb, Cd, Cr, Mn, Ni, Zn, and Cu was 0.02–0.45, Not detectable (ND)-9.45, 0.00–0.51, 0.05–2.19, 0.28–43.43, Not detectable (ND)-5.80, 2.005–175.77, and 0.20–23.85 mg/kg of fresh vegetables respectively. The concentrations of As, Pb, and Cd were higher than the maximum allowable concentration (MAC) in the vegetables. However, all the metals were consumed daily in amounts below the maximum tolerable daily intake (MTDI) for all vegetables. THQ values for all metals except As and Pb were below the safety level (THQ <1) in all the vegetables. Potential non-carcinogenic risk (THQ >1) was posed by As and Pb in some vegetables like cabbage, string bean, bottle gourd, green papaya, sponge gourd, etc. The TR levels of As, Cd, Cr, and Ni were higher than the acceptable levels (10−4) for most vegetables, suggesting that long-term exposure to these toxic metals may raise the risk of developing various malignancies, including stomach and lung cancer. An integrated approach is required to address the contamination burden to preserve the health of the consumers.